Improved handover authentication and key pre‐distribution for wireless mesh networks. (3rd August 2015) - Yang, Xu; Huang, Xinyi; Han, Jinguang; Su, Chunhua
Summary: Ticket‐based authentication is a critical technology to secure wireless mesh networks (WMN), which enable efficient communication among laptops, cell phones and other wireless devices. In this paper, we provide a new design of handoff authentication for WMN to reduce the delay caused by handoff. Our major improvement is on the key pre‐distribution for handoff authentication. We apply the attribute‐based encryption to encrypt key pre‐distribution messages for neighbor mesh routers. As a result, key pre‐distribution has constant computation and communication costs, which are independent of the number of neighbor mesh routers. Another advantage of our design is that it can perform immediate handoff authentication once the login authentication is complete, even before key pre‐distribution messages reach the foreign mesh router. The security of our handoff authenticator protocol is also improved by employing home mesh router's digital signature in the handoff ticket and key pre‐distribution messages. Our scheme can efficiently thwart forgery attacks. The proposed scheme provides an efficient and secure solution that meets the requirements of WMN in the era of Big Data. Copyright © 2015 John Wiley & Sons, Ltd.